Jože Javoršek in Matej Bor - Pirnat, Anja (Slavistična revija, 2020)
The article focuses on the period of correspondence between Jože Javoršek (1920-1990) and Matej Bor (1913-1993) from 1955 to 1988, based on what was possible to obtain from the Matej Bor's archive (Ms 1956) in the National and university library and some of the letters that have been kept by Javoršek's relatives. The analysis of the correspondence between the two authors, who began their acquaintance in a partisan cultural circle, shows a gradual development of their (friendly) relationship and their views of literature, culture in general, and the society of the time. The letters reveal the complications surrounding the 1965 Bled Congress; touch on Javoršek's trial, which was indirectly linked to his work Nevarna razmerja; and contain discussions about the future of the SASA (The Slovenian Academy of Sciences and Arts) and the recipients of the Prešeren Fund Award.
Keywords: 33. mednarodni kongres klubov PEN; 33rd International Congress of the PEN Clubs; Bor, Matej; cultural plenum of the Liberation front; Javoršek, Jože; kulturni plenum OF; literary critics; narodnoosvobodilni boj; national liberation war; pisemska zapuščina; Slovene dramatists; Slovene literature; Slovene poets; Slovene writers; slovenska književnost; slovenski dramatiki; slovenski literarni kritiki; slovenski pesniki; slovenski pisatelji; written correspondence archive